2007
DOI: 10.1016/j.appdev.2006.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The friendships of young children with developmental delays: A longitudinal analysis

Abstract: This longitudinal study examined the social interactions of children with mild developmental (cognitive) delays with friends across the early childhood and early elementary years. Results revealed increases in many forms of social exchange with effect sizes in the moderate range, but no changes in sustained interactive play. Social interaction patterns, difficulties in identifying friends to participate in the study, and concerns evident in children's peer and friendship networks suggest the general absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 37 publications
3
70
1
5
Order By: Relevance
“…It has been argued that interventions should be implemented as early as possible (Greer et al 2015;Guralnick et al 2007) to prevent long-term negative consequences. Therefore, it is imperative to know which approaches are preferred by younger students in primary schools.…”
Section: Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been argued that interventions should be implemented as early as possible (Greer et al 2015;Guralnick et al 2007) to prevent long-term negative consequences. Therefore, it is imperative to know which approaches are preferred by younger students in primary schools.…”
Section: Future Researchmentioning
confidence: 99%
“…Both the internationally accepted classification of students as having SEBD and the Dutch definition imply that SEBD will have a negative impact on students' social inclusion because of their characteristics. This negative impact might explain the lower levels of social inclusion of students with SEBD in the West compared to their peers with SEN (Guralnick et al 2007). Students with SEBD apply more frequently social problem-solving approaches such as physical and verbal aggression or withdrawal from social situations (Gumpel and Sutherland 2010;Kauffman and Landrum 2012;Newcomb, Bukowski, and Pattee 1993;Rose and Asher 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tie sa spájajú s príležitosťou dieťaťa rozvíjať si pozitívne vzťahy so svojimi rovesníkmi a začleňovať sa do spoločenského života (Scheepstra, Nakken, Pijl, 1999;Sloper, Tyler, 1992). Na druhej strane, medzinárodné štúdie opakovane ukázali, že zaradenie žiakov so ŠVVP nevedú automaticky k nárastu priateľstva medzi týmito žiakmi a ich rovesníkmi (Buysse, Davis Goldman, Skinner, 2002;Guralnick, Neville, Hammond, Connor, 2007;Lee, Yoo, Bak, 2003). Takéto sociálne vylúčenie môže viesť neskôr k úplnej izolácií v spoločenskom živote.…”
Section: Sociálny Aspekt Inkluzívneho Vzdelávaniaunclassified
“…For instance, Newcomb and Bagwell (1996) state that having at least one friend in class may serve as a buffer against the negative effects associated with low peer acceptance. This is especially important for low-performing students and students with special needs, since research has repeatedly shown that such students are less accepted than their typically developing peers (Buysse et al 2002;Guralnick et al 2007;Pearl et al 1998;Williams and Asher 1992). But typical peers can also experience a lack of acceptance and isolation in school settings (Pijl et al 2008;Koster et al 2010).…”
mentioning
confidence: 99%